Weeds survey and mapping at Chok Anan plot in UiTM Perlis farm / Mohamad Hairunizam Amir - Amir, Mohamad Hairunizam (Faculty of Plantation and Agrotechnology, 2014)
This study was conducted to identify, map out dominat weeds and evaluate the current and propose new weed management program in Chok anan plot of UiTM Perlis Farm. These study was conducted commencing from January 2014 until March 2014. Eight weeds species were identfied, Tridax procumbens, Asystasia Intrusa, Mimosa Pudica, Ageratum conyzoides, Ischaemum rogosum, Calapogonium mucunoides, Mimosa invisa and Paspalum conjugatum. Only seven weeds species were considered dominant in Chok anan plot excluding Paspalum conjugatum and weeds point distributions map and interpolation map were created to show the distributions of dominant weeds species by using ArcMap 10 software. From the evaluation of the dominant weeds in Chok anan plot in descending order were Tridax procumbens, Asystasia Intrusa, Mimosa Pudica, Ageratum conyzoides, Ischaemum rogosum, Calapogonium mucunoides, Mimosa invisa and Paspalum conjugatum. In the nutshells invasive weed species recorded the highest dominant level which depicted the seriousness of the weeds species in the Chokanan area. Current weeds management regimes failed to efficiently manage weed populations dynamics in the area and new weed management regimes such as precise weed management or intergrated weeds management is needed to manage weed population dynamics in the Chok anan plot in UiTM Perlis.